Maternal Exposure to Polychlorinated Biphenyls and Asthma, Allergic Rhinitis and Atopic Dermatitis in the Offspring: The Environmental Health Fund Birth Cohort - Berlin, Maya; Flor-Hirsch, Hadar; Kohn, Elkana; Brik, Anna; Keidar, Rimona; Livne, Ayelet; Marom, Ronella; Ovental, Amit; Mandel, Dror; Lubetzky, Ronit; Factor-Litvak, Pam; Tovbin, Josef; et al. (Frontiers in Pharmacology, 2022)
Background: Polychlorinated biphenyls (PCBs) are persistent organic pollutants banned for use worldwide. Due to their biodegradation resistance, they accumulate along the food chain and in the environment. Maternal exposure to PCBs may affect the fetus and the infant. PCBs are immunotoxic and may damage the developing immune system. PCBs are associated with elevated IgE antibodies in cord blood and are considered to be predictive of atopic reactions. Several studies on the association between prenatal exposure to PCBs and atopic reactions were previously published, albeit with conflicting results. Objectives: To examine the association between maternal PCBs levels and atopic reactions in their offspring. Methods: During the years 2013-2015, a prospective birth cohort was recruited at the delivery rooms of Shamir Medical Center (Assaf Harofeh) and "Dana Dwek" Children's Hospital. Four PCBs congeners were investigated: PCBs 118, 138, 153, and 180. In 2019, when children reached the age of 4-6 years, mothers were interviewed using the ISAAC questionnaire to assess symptoms of atopic reactions, including asthma, allergic rhinitis, and atopic dermatitis. Results: One hundred and fifty mother-child dyads were analyzed. No significant differences were found in the median serum PCBs concentrations of each studied congener or total PCBs for asthma, allergic rhinitis, atopic dermatitis diagnosis, or parent-reported symptoms. No association was found between exposure to Sum PCBs and the risk for asthma symptoms or diagnosis, adjusted to maternal age and family member with atopic condition: aOR=0.94, 95%CI: (0.88;0.99). No association was observed between each studied PCB congener and asthma symptoms or diagnosis. The same results were found also for other studied outcomes – allergic rhinitis and atopic dermatitis Conclusions: Our study joins a series of previous studies that attempt to shed light on environmental exposures in utero as influencing factors for atopic conditions in children. Our results reflect the complexity of the pathophysiology of these phenomena. No relationship between maternal serum PCBs levels was demonstrated for asthma, allergic rhinitis, or atopic dermatitis. However, additional multi-participant studies, with longer, spanning into later pediatric age follow up are needed.